City council member Blanca Alvarado meets Cesar Chavez. - Sahl, Ted (photographer):::Creator::::::::::::
City council member Blanca Alvarado shakes hands with Cesar Chavez at the 20th anniversary celebration of the United Farm Workers of America (UFW) labor union held at the Sacred Heart Church in San Jose, California.